CENTRIC RELATION BETWEEN CHIMERA AND REALITY- A NARRATIVE REVIEW - Alina Mihaela Apostu; Oana Tanculescu; Alice-Arina; Carina Balcos; Zenaida Surlari (Romanian Society of Oral Rehabilitation, 2023)
Introduction: The multitude of definitions for the centric relation (CR) has sparked extensive scientific debates, marking significant milestones in the evolution of concepts in these fields. The discourse surrounding CR has remained contentious for over a century, and there is still a persistent divergence of perspectives. Aim: This narrative review aims to unravel the evolutionary trajectory of CR definitions, seeking to untangle the existing confusion prevalent within specialized literature. Moreover, it endeavors to provide guiding principles within this contentious domain, offering valuable insights to practitioners, students, educators, and researchers. Discussion: Dentistry has not arrived at a consensus definition and concept of CR. Even in the era of evidence-based dentistry, CR still leaves room for controversy. Conclusion: The evolution of the CR concept and its definition, progressing from the exact specification of the maxillomandibular relationship, temporomandibular joint elements, and hinge axis and to its partial "abandonment" due to the individuality and particularities of the patients, should be contextualized within the functional and adaptable nature of the stomatognathic system.